1994
DOI: 10.1007/bf00194968
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol malabsorption caused by sitostanol ester feeding and neomycin in pravastatin-treated hypercholesterolaemic patients

Abstract: Serum cholesterol values were insufficiently reduced by pravastatin in two different patient populations. Therefore, we studied whether further cholesterol reduction could be achieved by inhibiting both cholesterol synthesis (by pravastatin) and absorption (by neomycin or sitostanol ester). Thus, we measured serum cholesterol, cholesterol precursors (reflecting cholesterol synthesis), cholestanol and plant sterols (reflecting cholesterol absorption and biliary secretion) for up to 6 weeks in pravastatin-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…A series of randomised, controlled trials [74][75][76] combining phytosterols with statin medication show a 4.5±2.4% additive effect, which translates to an additional 9-14% reduction in cardiovascular events, using risk modelling equations [77,78]. Accordingly, statin-induced inhibition of cholesterol synthesis may insufficiently reduce LDL cholesterol, produce adverse effects and may be uneconomical, such that suboptimal doses may be required [79].…”
Section: Phytosterol and Statin Combinationsmentioning
confidence: 98%
“…A series of randomised, controlled trials [74][75][76] combining phytosterols with statin medication show a 4.5±2.4% additive effect, which translates to an additional 9-14% reduction in cardiovascular events, using risk modelling equations [77,78]. Accordingly, statin-induced inhibition of cholesterol synthesis may insufficiently reduce LDL cholesterol, produce adverse effects and may be uneconomical, such that suboptimal doses may be required [79].…”
Section: Phytosterol and Statin Combinationsmentioning
confidence: 98%
“…Effects of combination therapy with plant sterols and/or stanols and statins Vanhanen (35) was the first to conduct a clinical trial towards the effects of sitostanol esters on lipid levels in patients on pravastatin treatment. It was found that the daily addition of 1·5 g sitostanol ester did not lower serum total or LDL-cholesterol after 6 weeks of supplementation.…”
Section: Mechanism Of Supporting Statin Therapymentioning
confidence: 99%
“…These authors suggest that plant sterols and stanols have an additive (35) DB, PC, R 3 HC on pravastatin therapy $ 1 year (n 14)…”
Section: Mechanism Of Supporting Statin Therapymentioning
confidence: 99%
“…The first study to examine combined treatments used a low dose of phytosterols (0.9 g/d) and showed no further reduction in LDL cholesterol with phytosterol addition. 102 When consumed at higher doses (1.8-3.0 g/d), phytosterol addition to statin therapy lowered LDL cholesterol an additional 6%-20%. [103][104][105][106][107][108][109][110][111] Because these studies were relatively short term lasting 4-12 weeks, De Jong et al 112 …”
Section: Statinsmentioning
confidence: 99%